Vibration-damping rubber composition for electric vehicles and vibration-damping rubber member for electric vehicles
The vibration-proof rubber composition for electric vehicles, incorporating natural rubber, terminally modified butadiene rubber, and specific types of carbon black, addresses the challenge of high dynamic magnification in high rigidity regions, achieving low magnification and durability.
Patent Information
- Application Number
- JP2023164217
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing vibration-proof rubber compositions for electric vehicles face challenges in achieving low dynamic magnification in high rigidity regions, despite the use of carbon black and blends of natural and terminally modified butadiene rubber.
A vibration-proof rubber composition for electric vehicles is formulated with natural rubber, terminally modified butadiene rubber, and surface-active carbon black with high hydrogen generation capacity, along with additional carbon black with low iodine adsorption, to achieve optimal static and dynamic spring constants.
The composition effectively reduces dynamic magnification in high rigidity regions while maintaining excellent durability, making it suitable for electric vehicle applications.
Smart Images

Figure 2025054959000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-vibration rubber composition for electric vehicles and an anti-vibration rubber member for electric vehicles. [Background technology]
[0002] Anti-vibration rubber compositions are used in automobiles to reduce vibration and noise. Such anti-vibration rubber compositions are required to have high rigidity and high strength in their vulcanizates (anti-vibration rubber components) and to suppress vibration transmission, so the value of the dynamic magnification [dynamic spring constant (Kd100) / static spring constant (Ks)] must be small (low dynamic magnification). Electric vehicles are heavier than gasoline-powered vehicles, so anti-vibration rubber components are required to have higher durability. Therefore, it is important to have a low dynamic magnification in the high rigidity (large static spring constant) region.
[0003] Conventionally, measures to reduce the dynamic magnification have been taken, for example, by using carbon black as a reinforcing agent in an anti-vibration rubber composition and controlling factors such as the amount of carbon black blended, particle size, structure, etc. (e.g., Patent Document 1). Patent Document 2 discloses an anti-vibration rubber composition obtained by kneading a terminal-modified butadiene rubber and a natural rubber. According to Patent Document 2, by blending a terminal-modified butadiene rubber and a natural rubber, an anti-vibration rubber with a small dynamic magnification and high strength can be obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 7037986 [Patent Document 2] Japanese Patent Application Publication No. 08-269237 Summary of the Invention [Problem to be solved by the invention]
[0005] When carbon black is added to rubber to increase rigidity, the dynamic modulus tends to deteriorate. For this reason, even when compounding terminal-modified butadiene rubber with natural rubber, there is still room for further improvement.
[0006] The problem to be solved by the present invention is to provide an anti-vibration rubber composition for electric vehicles and an anti-vibration rubber member for electric vehicles that can achieve a low dynamic magnification in a high rigidity (large static spring constant) region. [Means for solving the problem]
[0007] In order to solve the above problems, the anti-vibration rubber composition for electric vehicles according to the present invention contains the following components (A) to (C). (A) Natural rubber (B) Terminally modified butadiene rubber (C) Surface-activated carbon black, which has a hydrogen emission value (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C.
[0008] The (C) may be contained in a larger amount in the (B) than in the (A). The mass ratio of the content of the (A) to the (B) may be 2.0 or more and 9.0 or less. The anti-vibration rubber composition for electric vehicles according to the present invention may further contain (D) carbon black having an iodine adsorption amount of 20 g / kg or less. The total amount of the (C) and the (D) may be 60 parts by mass or more and 100 parts by mass or less, relative to a total of 100 parts by mass of the (A) and the (B). The mass ratio of the content of the (D) to the (C) may be 0.5 or more and 2.0 or less. The static spring constant Ks of the anti-vibration rubber composition for electric vehicles according to the present invention may be 700 N / mm or more and 1000 N / mm or less.
[0009] The anti-vibration rubber member for electric vehicles according to the present invention is formed from a vulcanizate of the anti-vibration rubber composition for electric vehicles according to the present invention.
[0010] (1) The anti-vibration rubber composition for electric vehicles according to the present invention contains the following components (A) to (C): (A) Natural rubber (B) Terminally modified butadiene rubber (C) Surface-activated carbon black, which has a hydrogen emission value (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C.
[0011] (2) In the above (1), it is preferable that the (C) is contained in a larger amount in the (B) than in the (A).
[0012] (3) In the above (1) or (2), the mass ratio of the content of (A) to the content of (B) is preferably 2.0 or more and 9.0 or less.
[0013] (4) In any one of the above (1) to (3), it is preferable that the composition further contains the following component (D): (D) Carbon black having an iodine adsorption amount of 20 g / kg or less
[0014] (5) In the above (4), the total amount of (C) and (D) may be 60 parts by mass or more and 100 parts by mass or less, per 100 parts by mass of the total of (A) and (B).
[0015] (6) In the above (4) or (5), the mass ratio of the content of (D) to the content of (C) may be 0.5 or more and 2.0 or less.
[0016] (7) In any one of the above (1) to (6), the static spring constant Ks of the anti-vibration rubber composition for electric vehicles may be 700 N / mm or more and 1000 N / mm or less.
[0017] (8) The anti-vibration rubber member for electric vehicles according to the present invention is made of a vulcanizate of the anti-vibration rubber composition for electric vehicles according to any one of (1) to (7) above. Effect of the Invention
[0018] According to the anti-vibration rubber composition for electric vehicles according to the present invention, since it contains the above-mentioned components (A) to (C), it is possible to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.
[0019] Here, by including more of (C) in (B) than in (A), it becomes easier to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.
[0020] When the mass ratio of the content of (A) to the content of (B) is 2.0 or more and 9.0 or less, a low dynamic magnification is achieved in a high rigidity (large static spring constant) region, while excellent durability is also achieved.
[0021] Furthermore, by containing (D) carbon black having an iodine adsorption of 20 g / kg or less, it is easy to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.
[0022] Furthermore, when the total amount of (C) and (D) is 60 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the total of (A) and (B), it is easy to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.
[0023] When the mass ratio of the content of (D) to the content of (C) is 0.5 or more and 2.0 or less, a low dynamic magnification is achieved in a high rigidity (large static spring constant) region, while excellent durability is also achieved.
[0024] If the static spring constant Ks is 700 N / mm or more and 1000 N / mm or less, it is suitable for use in an electric vehicle.
[0025] Furthermore, since the anti-vibration rubber member for electric vehicles according to the present invention is composed of a vulcanizate of the anti-vibration rubber composition for electric vehicles according to the present invention, a low dynamic magnification can be achieved in a high rigidity (large static spring constant) region. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The anti-vibration rubber composition for electric vehicles and the anti-vibration rubber member for electric vehicles according to the present invention will be described in detail below.
[0027] The anti-vibration rubber composition for electric vehicles according to the present invention (hereinafter sometimes simply referred to as anti-vibration rubber composition) contains the following components (A) to (C). (A) Natural rubber (B) Terminally modified butadiene rubber (C) Surface-activated carbon black, which has a hydrogen emission value (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C.
[0028] The natural rubber (A) is the main component of the rubber component of the anti-vibration rubber composition. The main component of the rubber component refers to a component that accounts for 50% by mass or more of the entire rubber component of the anti-vibration rubber composition. The natural rubber (A) is excellent in processability and mechanical strength (durability). The anti-vibration rubber composition is greatly influenced by the properties of the natural rubber (A), which is the main component of the rubber component.
[0029] The terminal-modified butadiene rubber (B) is a butadiene rubber whose molecular terminals are modified with an appropriate compound. As a modifier, metal salts such as tin tetrachloride (see "Japan Rubber Association Journal," Vol. 63, No. 5 (1990), pp. 27-33) have been known. It is also known to use lactam compounds as modifiers (for example, Nagata, "Japan Rubber Association Journal," Vol. 62, No. 10 (1989), pp. 38-48). The modifier is not particularly limited, but by blending lactam-modified butadiene rubber with natural rubber, particularly excellent improvement in vibration-proofing properties is observed. Since the terminal-modified butadiene rubber (B) alone has low strength and poor durability, it cannot be used alone, and the terminal-modified butadiene rubber (B) is blended with natural rubber (A), which has excellent processability and mechanical strength properties (durability). When butadiene rubber is used in combination with natural rubber (A), the dynamic magnification is reduced. By using terminal-modified butadiene rubber (B) in combination, the dynamic magnification can be further reduced.
[0030] The mass ratio of the content of (A) to (B) is preferably 2.0 or more and 9.0 or less. More preferably, it is 2.5 or more and 8.0 or less, and further preferably, it is 3.0 or more and 6.0 or less. When the amount of the terminal-modified butadiene rubber (B) is large, the dynamic magnification ratio is likely to be low. On the other hand, durability and processability are likely to be reduced. When the mass ratio of the content of (A) to (B) is 2.0 or more and 9.0 or less, a low dynamic magnification ratio is achieved in a high rigidity (large static spring constant) region, while excellent durability is also achieved.
[0031] The surface active carbon black (C) can contribute to lowering the dynamic magnification without lowering the rigidity (static spring constant or rubber hardness) of the vibration-proof rubber composition. The high rigidity region refers to a region where the static spring constant Ks (N / mm) is 700N / mm or more. More preferably, the static spring constant Ks (N / mm) is 750N / mm or more. As described above, the surface active carbon black (C) has a value (Hc) of 4500ppm or more, calculated as the amount of hydrogen generated when heated to 1980°C per gram of carbon black. If the Hc is 5000ppm or more, it is preferable because it has better surface activity. The amount of hydrogen is derived from hydrogen atoms of organic groups, such as hydroxyl groups and carboxy groups, that are covalently bonded to carbon atoms of the carbon black.
[0032] Since surface active carbon black (C) has many functional groups such as hydroxyl groups and carboxyl groups, it has a strong interaction with the terminally modified butadiene rubber (B), and there is more of it in the terminally modified butadiene rubber (B) than in the natural rubber (A). This reduces the friction between the rubber component and the carbon black, allowing for a lower dynamic magnification. The dispersion state of surface active carbon black (C) in the rubber can be observed with a transmission electron microscope (TEM).
[0033] The measurement of the amount of hydrogen is carried out, for example, as follows. That is, first, in order to remove the adsorbed components of the carbon black, 20 mg of carbon black, which has been degassed and dried in a vacuum dryer at 125°C for 4 hours, is placed in a tin capsule, and a high-sensitivity hydrogen analyzer (EMGA-621 manufactured by Horiba, Ltd., using a TCD detector) is used to thermally decompose the carbon black in a graphite crucible at 1980°C for 70 seconds. Then, the generated gas is passed through a high-temperature oxidizing agent, a room-temperature oxidizing agent, a carbon dioxide removing agent, and a desiccant by a carrier gas (inert argon gas) at a constant flow rate (400 ml / min), and separated in a column. Then, the hydrogen gas obtained is quantified by a detector (thermal conductivity method).
[0034] The surface active carbon black (C) may be used alone or in combination of two or more kinds, so long as it has the above-mentioned hydrogen amount.
[0035] From the viewpoints of durability and low dynamic magnification, the surface active carbon black (C) preferably has an iodine adsorption of 14 g / kg or more and 28 g / kg or less. The iodine adsorption of the carbon black is a value measured in accordance with JIS K 6217-1 (Method A). Moreover, from the viewpoints of durability and low dynamic magnification, the surface active carbon black (C) preferably has a DBP absorption of 118 ml / 100 g or more and 132 ml / 100 g or less. The DBP absorption of the carbon black is a value measured in accordance with JIS K 6217-4.
[0036] The anti-vibration rubber composition according to the present invention may further contain carbon black (D) having an iodine adsorption of 20 g / kg or less. The carbon black (D) is a surface-inactive carbon black. By using carbon black (D) having an iodine adsorption of 20 g / kg or less together with surface-active carbon black (C), it is easy to achieve a low dynamic magnification in a high rigidity (high static spring constant) region. The iodine adsorption of carbon black (D) is more preferably 10 g / kg or more and 20 g / kg or less, and even more preferably 15 g / kg or more and 20 g / kg or less. In addition, carbon black (D) preferably has a DBP absorption of 50 ml / 100 g or less. More preferably, it is 30 ml / 100 g or more and 50 ml / 100 g or less.
[0037] The total amount of (C) and (D) is preferably 60 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the total of (A) and (B). When the total amount is 60 parts by mass or more, the static spring constant is large and it is easy to achieve high rigidity. From this viewpoint, the content is more preferably 65 parts by mass or more, and even more preferably 70 parts by mass or more. On the other hand, when the content is 100 parts by mass or less, the dynamic spring constant is kept small in the high rigidity (large static spring constant) region, and it is easy to satisfy a low dynamic magnification ratio in the high rigidity (large static spring constant) region. From this viewpoint, the content is more preferably 95 parts by mass or less, and even more preferably 90 parts by mass or less.
[0038] The mass ratio of the content of (D) to that of (C) is preferably 0.5 or more and 2.0 or less, from the viewpoints of achieving excellent low dynamic magnification in a high rigidity (large static spring constant) region and excellent durability.
[0039] The anti-vibration rubber composition according to the present invention may contain additives, etc., in addition to the above components (A) to (C) or (A) to (D). Examples of the additives include vulcanizing agents, vulcanization accelerators, vulcanization aids, antioxidants, and process oils.
[0040] Examples of the vulcanizing agent include sulfur (powdered sulfur, precipitated sulfur, insoluble sulfur), and sulfur-containing compounds such as alkylphenol disulfides, etc. These may be used alone or in combination of two or more kinds.
[0041] The content of the vulcanizing agent is preferably in the range of 0.1 to 10 parts by weight, particularly preferably in the range of 0.3 to 5 parts by weight, based on 100 parts by weight of the total of (A) and (B). If the content of the vulcanizing agent is too low, crosslinking reactivity tends to deteriorate. If the content of the vulcanizing agent is too high, rubber properties (breaking strength, breaking elongation) tend to deteriorate.
[0042] Examples of the vulcanization accelerator include thiuram-based, sulfenamide-based, guanidine-based, thiazole-based, aldehyde ammonia-based, aldehyde amine-based, and thiourea-based vulcanization accelerators. These are used alone or in combination of two or more. Among these, a combination of a thiuram-based vulcanization accelerator and at least one vulcanization accelerator selected from the sulfenamide-based, guanidine-based, and thiazole-based vulcanization accelerators is preferred because it provides excellent compression set.
[0043] The content of the vulcanization accelerator is preferably in the range of 0.1 to 10 parts by weight, and particularly preferably in the range of 0.3 to 5 parts by weight, per 100 parts by weight of the total of (A) and (B).
[0044] Examples of thiuram vulcanization accelerators include tetramethylthiuram disulfide (TMTD), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetrakis(2-ethylhexyl)thiuram disulfide (TOT), tetrabenzylthiuram disulfide (TBzTD), and the like.
[0045] Examples of sulfenamide vulcanization accelerators include N-oxydiethylene-2-benzothiazolylsulfenamide (NOBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), Nt-butyl-2-benzothiazolesulfenamide (BBS), N,N'-dicyclohexyl-2-benzothiazolesulfenamide, etc. These may be used alone or in combination of two or more kinds.
[0046] Examples of the guanidine vulcanization accelerator include N,N'-diphenylthiourea, trimethylthiourea, N,N'-diethylthiourea, N,N'-dibutylthiourea, etc. These may be used alone or in combination of two or more kinds.
[0047] Examples of thiazole-based vulcanization accelerators include dibenzothiazyl disulfide (MBTS), 2-mercaptobenzothiazole (MBT), 2-mercaptobenzothiazole sodium salt (NaMBT), and 2-mercaptobenzothiazole zinc salt (ZnMBT). These are used alone or in combination of two or more. Among these, dibenzothiazyl disulfide (MBTS) and 2-mercaptobenzothiazole (MBT) are preferably used because of their excellent crosslinking reactivity.
[0048] Examples of the vulcanization aid include zinc oxide (ZnO), stearic acid, magnesium oxide, etc. These may be used alone or in combination of two or more.
[0049] The content of the vulcanization aid is preferably in the range of 0.1 to 10 parts by weight, and particularly preferably in the range of 0.3 to 7 parts by weight, per 100 parts by weight of the total of (A) and (B).
[0050] Examples of the antiaging agent include carbamate-based antiaging agents, phenylenediamine-based antiaging agents, phenol-based antiaging agents, diphenylamine-based antiaging agents, quinoline-based antiaging agents, imidazole-based antiaging agents, waxes, etc. These may be used alone or in combination of two or more kinds.
[0051] The content of the antioxidant is preferably in the range of 0.5 to 15 parts by weight, and particularly preferably in the range of 1 to 10 parts by weight, per 100 parts by weight of the total of (A) and (B).
[0052] Examples of process oils include naphthenic oils, paraffinic oils, aromatic oils, etc. These may be used alone or in combination of two or more.
[0053] The content of the process oil is preferably in the range of 1 to 35 parts by weight, and particularly preferably in the range of 3 to 30 parts by weight, per 100 parts by weight of the total of (A) and (B).
[0054] The anti-vibration rubber composition according to the present invention can be prepared by kneading the components (A) to (C) and other materials added as necessary using a kneading machine such as a kneader, a Banbury mixer, an open roll, or a twin-screw mixer.
[0055] The anti-vibration rubber composition according to the present invention becomes an anti-vibration rubber member (vulcanizate) by vulcanizing at high temperature (150 to 170°C) for 5 to 30 minutes. The anti-vibration rubber member made of the vulcanizate of the anti-vibration rubber composition according to the present invention can be advantageously used in applications such as motor mounts, suspension bushes, subframe mounts, and other anti-vibration rubbers for electric vehicles (including electric vehicles (EV), fuel cell vehicles (FCV), plug-in hybrid vehicles (PHV), hybrid vehicles (HV), and the like) that use electric motors as their power source.
[0056] According to the anti-vibration rubber composition of the present invention having the above-mentioned configuration, natural rubber (A) and terminal-modified butadiene rubber (B) are used together as the rubber components, and surface-active carbon black (C) is used for such rubber components, thereby achieving a low dynamic magnification in the high rigidity (large static spring constant) region. This is presumably because the surface-active carbon black (C) is contained in a larger amount in the terminal-modified butadiene rubber (B) than in the natural rubber (A), thereby reducing friction between the rubber component and carbon black, and the surface-active carbon black (C) contributes to a low dynamic magnification in the high rigidity region with a large static spring constant.
[0057] In the anti-vibration rubber composition according to the present invention, from the viewpoint of suitability for electric vehicles, the static spring constant Ks is preferably 700 N / mm or more and 1000 N / mm or less. More preferably, it is 750 N / mm or more and 1000 N / mm or less. By configuring the anti-vibration rubber composition according to the present invention as described above, the static spring constant Ks can be set within the above range.
[0058] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the spirit of the present invention. EXAMPLES
[0059] The present invention will now be described in detail with reference to experimental examples.
[0060] The materials used are as follows: <Diene rubber> Natural rubber (NR) (A) Terminally modified butadiene rubber (terminally modified BR) (B): Modifier: ε-caprolactam, polymer viscosity: 50, cis-1,4 / trans-1,4 / vinyl ratio = 39 / 49 / 12 <Surface active carbon black (C)> Surface-active carbon black (surface-active CB): SPHERON5200 manufactured by Cabot Japan (Hc: 5200ppm, iodine adsorption 24g / kg, DBP absorption 124ml / 100g) <Carbon black (D)> ·CB <1> : Tokai Carbon's "Seast TA", iodine adsorption capacity 18g / kg, DBP absorption capacity 42ml / 100g) <Other> ·CB <2> : Tokai Carbon's "Seast SO", iodine adsorption capacity 44g / kg, DBP absorption capacity 115ml / 100g) Zinc oxide: Sakai Chemical Industry's "Zinc oxide type 2" Stearic acid: Kao's "Lunacc S30" Process oil: Sansen 4130 made by Nippon San Oil Amine-based antioxidants <1> : Seiko Chemical's "Ozonone 6C" Amine-based antioxidants <2> : "Nonflex RD" manufactured by Seiko Chemical ·Vulcanization accelerator <1> : "Noccela CZ" manufactured by Ouchi Shinko Chemical ·Vulcanization accelerator <2> : "Noccela TBT" manufactured by Ouchi Shinko Chemical Sulfur (vulcanizing agent)
[0061] (Experimental Examples 1 to 7) The materials were mixed in the ratios (mass ratios) shown in the table, and then mixed using an internal mixer (Banbury type) or rolls to prepare rubber compositions. The properties of the prepared rubber compositions were measured and evaluated according to the following methods.
[0062] [Static spring constant (Ks)] Using each rubber composition, a rubber test piece was prepared by pressing and vulcanizing a disk-shaped metal fitting (diameter 60 mm, thickness 6 mm) onto the top and bottom surfaces of a rubber piece (diameter 50 mm, height 25 mm) under vulcanization conditions of 170°C x 30 minutes. Next, the rubber test piece was compressed 7 mm in the cylindrical axial direction, and the loads at deflections of 1.5 mm and 3.5 mm were read from the load-deflection curve of the second forward movement to calculate the static spring constant (Ks (N / mm)).
[0063] [Dynamic spring constant (Kd100)] The rubber test piece was compressed by 2.5 mm in the cylindrical axial direction, and a constant displacement harmonic compression vibration with an amplitude of 0.05 mm and a frequency of 100 Hz was applied from below centered on the position of this 2.5 mm compression. The dynamic load was detected by a load cell above, and the dynamic spring constant (Kd100 (N / mm)) was calculated in accordance with JIS K 6394.
[0064] [Dynamic magnification (Kd100 / Ks)] The dynamic magnification was calculated as the value of dynamic spring constant (Kd100) / static spring constant (Ks). Since the dynamic magnification is proportional to Ks, a rubber material with a lower dynamic magnification is preferable when the Ks is the same. Therefore, the dynamic magnification was evaluated (comparison of the superiority of the dynamic magnification) using the value obtained by dividing the dynamic magnification by Ks. Values of [dynamic magnification / Ks x 1000] of 1.90 or less were evaluated as "A," values between 1.90 and 2.05 or less were evaluated as "B," and values exceeding 2.05 were evaluated as "C."
[0065] [Durability] Each rubber composition was press molded (vulcanized) at 150°C for 30 minutes to produce a rubber sheet with a thickness of 2 mm. Then, a JIS No. 3 dumbbell was punched out from this rubber sheet, and a stretch fatigue test was performed using this dumbbell in accordance with JIS K 6260 to measure the number of times of durability. Those that had a durability of more than 4000 times were rated "A", those that had a durability of 2000 times or more and 4000 times or less were rated "B", and those that had a durability of less than 2000 times were rated "C".
[0066] [Table 1]
[0067] In Experimental Examples 1-5, natural rubber and terminal-modified butadiene rubber are used in combination as the rubber component, and surface-active carbon black is used as the carbon black for this rubber component. In Experimental Example 6, only natural rubber is used as the rubber component. In Experimental Example 7, natural rubber and terminal-modified butadiene rubber are used in combination as the rubber component, but only surface-inactive carbon black is used as the carbon black. These Experimental Examples show that by using natural rubber and terminal-modified butadiene rubber in combination as the rubber component and using surface-active carbon black as the carbon black for this rubber component, it is possible to achieve a low dynamic magnification in the high rigidity (large static spring constant) range.
[0068] Furthermore, from Experimental Examples 1-3, it can be seen that when the mass ratio of the content of natural rubber to the terminal-modified butadiene rubber is 2.0 or more and 9.0 or less, a low dynamic magnification is achieved in the high rigidity (large static spring constant) region while also achieving excellent durability.
[0069] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention.
Claims
1. The anti-vibration rubber composition for electric vehicles comprises the following components (A) to (C): (A) Natural rubber (B) Terminally modified butadiene rubber (C) A surface active carbon black having an amount of hydrogen generated when heated to 1980° C., calculated per gram of carbon black (Hc), of 4500 ppm or more.
2. 2. The anti-vibration rubber composition for electric vehicles according to claim 1, wherein the (C) is contained in a larger amount in the (B) than in the (A).
3. 3. The anti-vibration rubber composition for electric vehicles according to claim 1, wherein a mass ratio of the content of said (A) to the content of said (B) is 2.0 or more and 9.0 or less.
4. The anti-vibration rubber composition for electric vehicles according to claim 1 or 2, further comprising the following component (D): (D) Carbon black having an iodine adsorption amount of 20 g / kg or less
5. 5. The anti-vibration rubber composition for electric vehicles according to claim 4, wherein the total amount of (C) and (D) is 60 parts by mass or more and 100 parts by mass or less, per 100 parts by mass of the total of (A) and (B).
6. 5. The anti-vibration rubber composition for electric vehicles according to claim 4, wherein a mass ratio of the content of said (D) to the content of said (C) is 0.5 or more and 2.0 or less.
7. 3. The anti-vibration rubber composition for electric vehicles according to claim 1 or 2, wherein the static spring constant Ks is 700 N / mm or more and 1000 N / mm or less.
8. The (C) is contained in a larger amount in the (B) than in the (A), The mass ratio of the content of (A) to the content of (B) is 2.0 or more and 9.0 or less, Further, (D) carbon black having an iodine adsorption amount of 20 g / kg or less is contained, The total amount of (C) and (D) is 60 parts by mass or more and 100 parts by mass or less with respect to 100 parts by mass of the total of (A) and (B), The mass ratio of the content of (D) to the content of (C) is 0.5 or more and 2.0 or less, 2. The anti-vibration rubber composition for electric vehicles according to claim 1, having a static spring constant Ks of 700 N / mm or more and 1000 N / mm or less.
9. 2. An anti-vibration rubber member for electric vehicles, comprising a vulcanizate of the anti-vibration rubber composition for electric vehicles according to claim 1.
Citation Information
Patent Citations
Vibration-proofing rubber composition
JP1996269237A
Anti-vibration rubber composition for electric vehicles and anti-vibration rubber member for electric vehicles
JP7037986B2